Analysis of Bacterial Load in Pre and Post-Filtered Drinking Water at the Educational Institutions of Rabwah, District Chiniot, Pakistan - Mirza Naseer Ahmad; Saad Sattar; Jaleed S. Ahmad; Rashida Sultana (International Journal of Economic and Environmental Geology, 2018)
Water-borne diseases mainly are due to bacterial contamination which mostly cause mortality among children of developing countries. The main objective of the study was to evaluate the bacterial load in the drinking water of educational institutions in Rabwah, district Chiniot and to evaluate different filters to provide clean drinking water. Samples were collected on a monthly basis for continuous 12 months (April 2016 – March 2017) from 15 educational institutions before and after the filtration process to check the effectiveness of the installed filters.Each sample was processed for the analysis of total bacterial load, the detection of Gram-ve bacteria as well as E.coliby plate detection method. Confirmatory biochemical tests were performed for the detection of E.coli. Results showed that pre-filtered samples were relatively more contaminated with bacteria than the post-filtered ones. The frequency of occurrence of bacterial load decreases in post-filtered samples, yet it is not always zero. This may be due to inappropriately installed filters. Different types of cleaning and filtering techniques such as ozone, chlorination and UV radiations were tested to remove bacterial contamination. The recommended amount of chlorination and passing of ozone for 15 minutes successfully eradicatedmicrobiological contamination in drinking water. The effectiveness of UV radiationin killing pathogens depends upon the amount of bacterial load in the water and exposure time of the UV radiation. Less exposure time of the UV radiations could not successfully remove the bacterial contamination. Therefore, UV radiation filter may not be effective at public places such as schools, where drinking water is extensively used and exposure time is not sufficient.